2007
DOI: 10.1002/ajpa.20599
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of the human sacrum: Anthropological perspectives and methodological approaches

Abstract: Discovering the nature of sacral orientation is of considerable anthropological importance. Therefore, this study aims at presenting a new anthropologically based definition for sacral anatomical orientation (SAO) angle, establishing standards of SAO for human population; examining the relationship between pelvic incidence (PI) and SAO; and associating SAO with demographic parameters. The study population consisted of 424 adult and 14 sub-adult (13-18 years, for SAO only) pelvises. Sacral orientation was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0
14

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 34 publications
(58 reference statements)
4
44
0
14
Order By: Relevance
“…These three variables are angular position-independent anatomical parameters. In modern humans, the SAO has been found to be strongly and negatively correlated with the PI (r = −0.824) (26). Modern humans also show significantly positive correlations between the pelvic anatomical parameter PI and the positional parameter sacral slope (SS) (r = 0.63-0.86) that in turn is also significantly positively correlated with the positional parameter lumbar lordosis (LL) (r = 0.68-0.89).…”
Section: )mentioning
confidence: 99%
“…These three variables are angular position-independent anatomical parameters. In modern humans, the SAO has been found to be strongly and negatively correlated with the PI (r = −0.824) (26). Modern humans also show significantly positive correlations between the pelvic anatomical parameter PI and the positional parameter sacral slope (SS) (r = 0.63-0.86) that in turn is also significantly positively correlated with the positional parameter lumbar lordosis (LL) (r = 0.68-0.89).…”
Section: )mentioning
confidence: 99%
“…Authors using relatively younger subjects; but significant increases in lumbar lordotic angle with age. However, 11,20,25 any significant association between lumbar lordosis and age. The higher standing of the Coefficient of variation in the younger age group and the significant association between lumbar curvature and old age, is remodeling through the mechanism of osteoclasts osteoblasts, as opposed to degenerative changes in the older age group, with greater involvement This study consisted mainly of young adults, middle age and the old adults.…”
Section: Discussionmentioning
confidence: 89%
“…17 , in his study of 105 Nigerians, using a flexi curve, found an increase in the thoraco lumbar curvature of more than 20% in Nigerians compared to Caucasians. To the contrary, 17,18 the greater curvature seen in African Americans is due to greater buttock size, whereas lumbar lordosis angle of 61 0 in whites By way of single variable calculus, and using table 3 and figure 2, a probability density function curve he cumulative sum of the frequency of a given angle, summed progressively over successive angles and then multiplying by 100/N(300) was constructed(figure3), using the om table 2 An increase in lumbar lordotic angle was observed from 18 years, to 37 years, with a plateau about age 47 to 67 years investigation also demonstrated significant age related differences in lumba lordosis angle, which were observed between different age groups particularly 58-77 years (Table3 flexibilities in the degree of lordosis in age were noted by 20 gradual increase in lumbar lordotic angle up to middle age followed by a decrease. This result is also similar to the works of statistically significant variation in lordosis angle of different age groups, with older individuals showing higher values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations